Experimental comparison of the Butler-Volmer and Marcus-Hush-Chidsey formalisms of electrode kinetics: The reduction of cyclooctatetraene at mercury hemispherical electrodes via cyclic and square wave voltammetries - Suwatchara, D; Rees, N; Henstridge, M; Laborda, E; Compton, R (2012)
Critical analysis of the Butler-Volmer and Marcus-Hush-Chidsey kinetic models is carried out through the study of the first one-electron reduction of cyclooctatetraene in DMSO at mercury hemispherical microelectrodes. This is an atypically slow process due to the conformational distortion taking place from the tub-shaped neutral species to the planar radical anion. Cyclic and square wave voltammetries are employed with the aim of examining the consistency of the results extracted from each model. Whereas the experimental results in cyclic voltammetry are adequately fitted by both models, the fit of square wave voltammograms at high frequency are not satisfactory when the Marcus-Hush-Chidsey formalism is employed. © 2011 Elsevier B.V. All rights reserved.